An Overview of Agricultural Pollution in the Philippines : The Fisheries Sector 2016 - World Bank (World Bank, Washington, DC, 2018)
This report is part of a national overview of agricultural pollution in the Philippines, commissioned by the World Bank. The overview consists of three ‘chapters’ on the crops, livestock, and fisheries sub-sectors, and a summary report. This ‘chapter’ provides a broad national overview of: (a) the magnitude, impacts, and drivers of pollution related to the fisheries sector’s development with a focus on aquaculture; (b) measures that have been taken by the public sector to manage or mitigate this pollution; and (c) existing knowledge gaps and directions for future research. This report was prepared on the basis of existing literature, recent analyses, and national and international statistics, as well as extensive interviews. It did not involve new primary research and did not attempt to cover pollution issues that arise in the broader aquaculture value chain, relating for instance to processing, packaging and transportation, feed processing, or veterinary drug factories.